Legal aspect of medical practice: A sojourn - Rajesh Harsvardhan; Rishabh Kumar; Ayush Mehrotra (Wolters Kluwer -Medknow Publications, 2022)
The Consumer Protection Act (CPA), 1986 evolving over the strands of time by legal and judicial proceedings has given the consumers of healthcare services a legal recourse to air their grievances. Although it is important to punish guilty medical professionals, it is also equally important to protect medical professionals who act in good faith from harassment. Hence, courts need to strike a perfect balancing act.